Civil society in Central Asia - Ruffin, M. Holt; Waugh, Daniel Clarke (University of Washington Press, 1999)
Covering Kazakhstan, Uzbekistan, Turkmenistan, and, Tajikistan, these 12 essays (drawn from a 1998 conference sponsored by the Center for Civil Society International) explore the prospects of and dangers facing the growth of Western-style democracy in Central Asia. Reflecting a range of disciplines and perspectives, the articles touch upon such topics as the role of environmental NGOs, the realization of freedom of association, prospects for an independent media, and the emergent role of Islam in the area. Annotation c. Book News, Inc., Portland, OR (booknews.com).